(untitled) (Journal of Dhaka Medical College, 2021)
Background: Esophageal cancer is one of the most serious gastrointestinal cancer worldwide, owing to its rapid development and fatal prognoses in most cases. There is a paucity of published data regarding esophageal cancer the study area in particular. This study was conducted to describe the endoscopic and clinicopathological patterns of esophageal cancer in this part of the world. The study provides baseline local data for future comparison. Objectives: The present study is done to highlight the increasing incidence of oesophageal cancer in the population. Methods: Detailed informations were obtained in each cases according to protocol. Complete history was taken either from patient or accompanying attendants. Thorough clinical examination was done. Relevant investigation reports were collected. All the informations were recorded according to fixed protocol. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS version 19. Results: Among the 50 cases, mean age was 52.92(±10.60) years, minimum age was 30 years and maximum age was 80 years. Maximum 76% were male and 24% were female, male: female ratio was 3.17:1. Socio-economic status of the study population, majority 48% were of lower middle class and 40% were of lower class. Common clinical presentations were dysphagia, regurgitation, significant weight loss and nausea and vomiting which were 100%, 96%, 80% and 14% respectively. Common personal history were smoking, white tobacco chewing, betel nut, betel leaf and alcohol consumption which were 66%, 20%, 92%,92% and 10% respectively. Anatomical site of oesophageal cancer, 48% were middle and lower third oesophageal cancer each. Histopathological type of oesophageal cancer, majority 56% were squamous cell carcinoma of different grades and 40% were adenocarcinoma of different grades. Common clinical staging (TNM) of the oesophageal cancer, T2 disease was 58% followed by T3, 26% and T1, 6%. Considering nodal status most of the cases were NO, 60% with Ni, 24% and N2, 16%. Regarding metastasis, only 18% cases had evidence of metastasis. Regarding treatment options of the esophageal cancer, majority 76% were selected for operative procedure, 10% for chemotherapy, 2% for radiotherapy and the rest of 12% for palliation. Conclusion: In conclusion, common clinical presentations of oesophageal cancer were dysphagia, regurgitation, significant weight loss and nausea and vomiting. Predominant personal history were smoking, white tobacco chewing, betel nut, betel leaf and alcohol consumption. Most of the oesophageal cancers were middle and lower third. Majority of oesophageal cancers were squamous cell carcinoma of different grades. Regarding TNM staging most of the oesophageal cancers were T2 disease. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 69-76